2020
DOI: 10.5606/tgkdc.dergisi.2020.18659
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of blood amount used in pleurodesis to prevent prolonged air leakage

Abstract: Bu çalışmada sekonder spontan pnömotorakslı hastalarda otolog kan yama plörodezinde kullanılan farklı kan miktarlarının klinik sonuçlar üzerindeki etkileri araştırıldı.Ça lış ma pla nı: Ocak 2015 -Nisan 2019 tarihleri arasında kliniğimizde tedavi edilen ve yedi günü geçmiş inatçı hava kaçağı olan sekonder spontan pnömotorakslı toplam 42 hasta (36 erkek, 6 kadın; ort. yaş 52.1±16.0 yıl; dağılım, 25-83 yıl) retrospektif olarak değerlendirildi. Hastalar 60 mL otolog kan yama plörodezi yapılanlar (Grup 1, n=20) ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Droghetti et al 16 used larger volumes (100–150 ml) of autologous blood and observed that the pneumothorax was resolved earlier compared with reported cases that used smaller volumes of autologous blood. Akar et al 29 compared patients who were injected with either 60 ml or 120 ml of autologous blood, respectively, and the results confirmed that patients who received 120 ml of autologous blood had significantly shorter pneumothorax leakage and extubation times compared with the times reported for patients in the 60 ml group. 29 In the Guo et al 30 study, the patients were divided into four groups that received 0.5 ml/kg, 1 ml/kg, or 2 ml/kg of autologous blood or sterile normal saline, respectively.…”
Section: Discussion and Literature Reviewmentioning
confidence: 88%
See 1 more Smart Citation
“…Droghetti et al 16 used larger volumes (100–150 ml) of autologous blood and observed that the pneumothorax was resolved earlier compared with reported cases that used smaller volumes of autologous blood. Akar et al 29 compared patients who were injected with either 60 ml or 120 ml of autologous blood, respectively, and the results confirmed that patients who received 120 ml of autologous blood had significantly shorter pneumothorax leakage and extubation times compared with the times reported for patients in the 60 ml group. 29 In the Guo et al 30 study, the patients were divided into four groups that received 0.5 ml/kg, 1 ml/kg, or 2 ml/kg of autologous blood or sterile normal saline, respectively.…”
Section: Discussion and Literature Reviewmentioning
confidence: 88%
“…Akar et al 29 compared patients who were injected with either 60 ml or 120 ml of autologous blood, respectively, and the results confirmed that patients who received 120 ml of autologous blood had significantly shorter pneumothorax leakage and extubation times compared with the times reported for patients in the 60 ml group. 29 In the Guo et al 30 study, the patients were divided into four groups that received 0.5 ml/kg, 1 ml/kg, or 2 ml/kg of autologous blood or sterile normal saline, respectively. The results showed that the success rates associated with the larger volumes (1 ml/kg and 2 ml/kg) were significantly higher than the 0.5 ml/kg group.…”
Section: Discussion and Literature Reviewmentioning
confidence: 88%
“…The advantages of this method are that it does not create chest pain during the application, is effective, and is nonimmunogenic 12 . However, by forming a clot in the chest tube during the procedure, it may prevent air drainage and lead to pressure pneumothorax 13,14 …”
Section: Discussionmentioning
confidence: 99%
“…12 However, by forming a clot in the chest tube during the procedure, it may prevent air drainage and lead to pressure pneumothorax. 13,14 The primary indication for the use of the PGA patch is to strengthen the suture line in operations involving the lung, bronchus, liver, and digestive system, and prevent air leaks. The PGA patch is surgically easy to apply and has different sizes and thicknesses.…”
Section: Discussionmentioning
confidence: 99%
“…The baseline characteristics of the included studies are summarized in Table 1. There were 18 studies included: six were retrospective [5][6][7][8][9][10], seven were randomized controlled trials (RCTs) [11][12][13][14][15][16][17], one study was a non-randomized controlled trial [18], three were prospective studies [19][20][21], and one was a case series involving 11 patients with original data [22]. The sample sizes of the included studies ranged from 11 to 167 [22,20].…”
Section: Study Characteristics and Quality Of The Included Studiesmentioning
confidence: 99%